Transcultural nursing in perioperative patient care. - Anna Kostka; Sylwia Krzemińska; Adriana Borodzicz; Sylwia Durlej-Kot; Mariusz Chabowski; Dariusz Janczak (Kazimierz Wielki University, 2017)
Jehovah's Witnesses is a religious association, who refuses blood transfusions even in life-threatening conditions. There are several alternative methods, implemented for use with patients that religion, whose task is to reduce the risk of bleeding and hemorrhage in the perioperative period. Good cooperation of the therapeutic team, the selection of appropriate treatment, the use of recommended methods of anesthesia, surgical techniques and proper nursing care with careful monitoring of post-operative complications and quick response if they leave, they contribute to the improvement of health.